(untitled) (Journal of Surgical Sciences, 2019)
Background: Urolithiasis may be associated with various degree of renal impairment secondaryto a combination of obstruction, urinary infection, long standing calculus, stone burden,frequent surgical intervention, and co-existing medical diseases. Objective: The purpose of the study is to predict the factors those have a significant impact foroutcome of the patients with renal impairment following treatment of urolithiasis. Methods: Fifty patients of urolithiasis with renal impairment were enrolled in this prospectivestudy, carried out between 1st July, 2008 and 30th June, 2009, at department of Surgery,Shaheed Ziaur Rahman Medical College Hospital, Bogra. Patients with renal impairment wasdefined as a baseline serum creatinine of >1.2mg/dl and/or on the basis of DTPA isotoperenogram findings (mild, moderate or severe impairment). Definite management was carriedout by means of open surgery, ESWL or in combinations available at study place. Follow-up after3 months, the postoperative renal functional outcome was defined as improved (>20% fall inserum creatinine), stabilized (<20% rise or <20% fall in serum creatinine), or deteriorated(>20% rise in serum creatinine). Renal function was also assessed by the impression madefrom the graph of DTPA isotope renogram (normal functioning or mild, moderate and severeimpairment). Predictive factors to be evaluated for the stone clearance and renal functionaloutcome were age of the patients, duration of symptomatology and urolithiasis, associateddiseases (hypertension and diabetes mellitus), stone burden, stone number and associatedurinary infection. Results: After 3 months of follow-up, the overall stone clearance rate was 76%. Out of 50patients, 27 patients (54%) showed improvement, 19 patients (38%) showed stabilization, and04 patients (08%) showed deterioration in their renal function. Age <40 years, duration ofsymptoms <6 months, stone burden <5 cm2 and single urinary stone were significant predictorsof subsequent good renal functional outcome. Conclusion: The renal recoverability rate after treatment of urinary stone disease could bepredicted by age, duration of symptoms, stone burden and stone number Journal of Surgical Sciences (2016) Vol. 20 (1) : 18-23